2015
DOI: 10.1177/0731684415595126
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal properties of sisal fiber reinforced acrylated epoxidized castor oil toughened diglycidyl ether of bisphenol A epoxy nanocomposites

Abstract: In this study, the bio-based epoxy nanocomposites were prepared from acrylated epoxidized castor oil toughened diglycidyl ether of bisphenol A epoxy network filled with sisal fibers and cloisite 30B clay. The chemical structure of acrylated epoxidized castor oil resin was confirmed by Fourier transform infrared and Proton nuclear magnetic resonance (1HNMR) spectroscope techniques. Mechanical and thermal properties of the sisal fiber reinforced acrylated epoxidized castor oil toughened diglycidyl ether of bisph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 31 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Meanwhile, at higher wt% of fillers, there was deterioration in the properties of the NFPCs, due to agglomeration of the fillers and the interfacial adhesion between the polymer matrix and fiber were noticed to be weak. Furthermore, it was suggested that the rise in tensile modulus and the fall in impact strength of the NFPCs with clay fillers were as a result of the polymer matrix improved cross-link density, which led to a decrease in the stiffness of the composite, hence reduced the impact strength [130,133]. While in other studies, aluminum powder was used as fillers and in others, modified clay improved the impact strength of the composite, as the SEM micrographs revealed the existence of less voids and rise in density along with improvement in stiffness resultant from better interfacial adhesion amongst the fiber and the matrix in the presence of the modified clay [134,135].…”
Section: Nanocellulose and Nanoparticlesmentioning
confidence: 99%
“…Meanwhile, at higher wt% of fillers, there was deterioration in the properties of the NFPCs, due to agglomeration of the fillers and the interfacial adhesion between the polymer matrix and fiber were noticed to be weak. Furthermore, it was suggested that the rise in tensile modulus and the fall in impact strength of the NFPCs with clay fillers were as a result of the polymer matrix improved cross-link density, which led to a decrease in the stiffness of the composite, hence reduced the impact strength [130,133]. While in other studies, aluminum powder was used as fillers and in others, modified clay improved the impact strength of the composite, as the SEM micrographs revealed the existence of less voids and rise in density along with improvement in stiffness resultant from better interfacial adhesion amongst the fiber and the matrix in the presence of the modified clay [134,135].…”
Section: Nanocellulose and Nanoparticlesmentioning
confidence: 99%
“…Traditionally, in order to improve mechanical properties, polymer composites are reinforced by aramid, glass, and carbon fibers . Considering environmental protection, the recent research interests are attracted to substitute the traditional fibers with natural ones, such as sisal fiber, which exhibits advantages mainly on green regeneration, low price (0.36 USD/kg, versus glass fiber’s 3.25 USD/kg), light weight (density: approximately 1.5 g/cm 3 ), and flexibility during processing which results in less abrasion on processing machinery. A lot of literatures studies mentioned its applications on polypropylene, phenolics, epoxy, and unsaturated polyester composites. …”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the fiber surface becomes cleaned and imparts the thermal stability of sisal fibers. 4043…”
Section: Resultsmentioning
confidence: 99%